AN OVERVIEW OF NURSES CARING BEHAVIOUR TOWARD PATIENT IN PATIENT WARD AT RSUD IN KLUNGKUNG REGENCY - Purniawati, Wayan; Dewi, Puja Astuti; Kamaryati, Ni Putu (Jurnal Riset Kesehatan Nasional, 2017)
Background: The behavior of the nurses in caring is form of emotional support of nurses in providing nursing care is moral commitment to protect, promote human dignity as the core of nursing that differentiates it from other professions.Purpose of the research: to know the overview of nurses caring behavior toward patients in patient treatment ward in Klungkung regency.Method: the design of the study wasdescriptive method purposive sampling techinique and proportionale stratified random sampling. The populationof the study was 308 people and the sample was 110 people. The  data collection tool was questionnaire CBA (Caring Behaviour Assesment)which has been modified. Data was analyzed using descriptive statistics and processed using SPSS 20.0 for windows.Result: The nurse caring behavior to patients in the ward showed 43,6%patients received good treatment, 52,7% patients received sufficient treatment and  3,7% patients received less treatment.Conclusion: Nurse that provided nursing care to patients should have caring behaviour in helping patients to meet their needs biologically, psychologically, sociologically and spritually Keywords: behavior, caring, inpatient, nurse